Synthesis of novel Sm3+ doped Li2O-Bi2O3-Al2O3-TeO2 glass system: optical properties, Judd-Ofelt analysis, and photoluminescence mechanism - Shah, A. Z.; Zaid, M. H. M.; Matori, K. A.; Loh, Z. W.; Hisam, R.; Cheong, W. M.; Wahab, S. A. A. (Elsevier B.V., 2024)
A new series of 20Li2O‒1Bi2O3‒5Al2O3‒(74-x)TeO2‒xSm2O3 glasses varying x with 0 to 2.0 mol%, was fabricated via the melt and quenching method. The X-ray diffraction confirmed the glass's amorphous nature, while utilizing FTIR absorption spectra, the relative areas of TeO4 and TeO3 were found in the range of 0.10695 to 0.19274 and 0.89305 to 0.80726, respectively, to justify the BO's and NBO's formation in the glass network. It is denoted that the BO is increasing with the progress of Sm3+ concentration even though the glass system is rich in NBO. The optical behavior of the glasses was investigated using UV-Visible, and photoluminescence spectroscopy. Through Tauc's plot analysis, the indirect band gap is increasing from 2.210 to 2.768 eV due to the BO's formation. The bonding parameter reveals the ionic bonding between Sm3+ ions and surrounding ligands. However, upon Sm3+ addition, a reduction in ionic bonding is observed. The calculated Judd-Ofelt, Ω2 displays a decreasing value ranging from 7.25 to 4.98 × 10-20cm2. The Judd-Ofelt oscillator strength reveals a reduction from 7.03 × 10-6 to 4 × 10-6 suggesting the increment of BOs in the host matrix has reduced the asymmetry and the covalency of the Sm3+ ion with the local environment ligand. Photoluminescence spectra excited at 410 nm reveal 4 major emission peaks of 4G5/2→6H5/2, 4G5/2→6H7/2, 4G5/2→6H9/2, and 4G5/2→6H11/2. The emission intensity has enhanced with Sm2O3 addition. However, above 1.5 mol% of Sm2O3 concentration, the emission decreased due to the luminescent quenching effect.